Evaluation of Growth Characteristics and Haematological Indices of Broiler-chicks Fed Raw and Processed Bambara Groundnut Seed as a Component of Poultry Feed - Oloyede, O.B.; Minari, J.B.; Muhammad, N.O. (International Journal of Poultry Science, 2010)
Sixty broiler chicks (day-old) were used in a 4-week feeding experiment to assess the growth response and heamatological variables of broilers-chicks fed raw, roasted and fermented bambara groundnut as a sole source of protein. Soybean based diet served as the control. There were four (4) experimental groups, each made up of five birds in three replicates, allocated to the experimental diets. The results showed that the average final live weight, average weekly weight gain and average feed intake of birds fed fermented bambara groundnut performed better than birds fed roasted bambara groundnut but demonstrated inferiority when compared to the control. Among other organs measured the relative weight of gizzard were significantly (p